(untitled) (Journal of actual problems of jurisprudence, 2018)
This article explores the coordinating role of the prosecution in the Republic of Kazakhstan. By securing a fight against crime prosecution authorities act not only as a supervisory authority, but as a coordinator. We consider the position of the Coordinating Council of the Republic of Kazakhstan, reviewed the provisions of the legislation of the Republic of Kazakhstan. Key words: Law enforcement agencies, prosecutor’s office, coordinating functions, crime, mutual exchange, investigation and inquiry.